The Impact of Obesity and Exercise on Cognitive Aging - Chan, John S.Y.; Yan, Jin H.; Payne, V. Gregory (Frontiers in Aging Neuroscience, 2013)
Obesity is a major concern in the aging population and degrades health, motor functions and cognition in older adults. The effects of obesity are pervasive and challenging to health-care systems, making this a widespread and critically important public health dilemma. In this review, we examine the relationship between obesity, cognitive aging, and related dysfunctions. Potential neural mechanisms underlying such relationship are described. We propose that cost-effective exercises can be employed to cope with obesity and cognitive declines in older adults. Finally, we discuss implications and future research directions.